Donafenib combined with sintilimab for advanced hepatocellular carcinoma: a single arm phase II trial - Xiaoyang Hong; Yongjian Guo; Wenbo Shi; Kangshun Zhu; Licong Liang; Liteng Lin; Ye Chen; Jingwen Zhou; Jingjun Huang; Jiabai Huang; Yaozhu Wu; Wensou Huang; et al. (BMC Cancer)
Abstract Background Previous studies evaluating antiangiogenic agents plus immune checkpoint inhibitors for unresectable hepatocellular carcinoma (HCC) have shown encouraging results. This study was conducted to investigate the efficacy and safety of donafenib combined with sintilimab (Don-Sin) for advanced HCC. Methods This was a single-center, single-arm phase II trial recruiting patients with BCLC stage C HCC. A safety run-in cohort was planned with the first 6 patients receiving oral donafenib 200 mg twice daily and intravenous sintilimab 200 mg once every 3 weeks. Dose-limiting toxicities (DLTs) were evaluated to determine the recommended dose of donafenib for those enrolled thereafter. The primary endpoint of this study was progression-free survival (PFS) per mRECIST. Results 30 patients were enrolled. As 3 patients (50.0%) experienced DLTs during safety run-in, the initial dose of donafenib was adjusted to 200 mg once daily for subsequent patients. The primary endpoint was met with a median PFS of 6.2 (95% confidence interval [CI], 4.4-8.0) months per mRECIST (6.3 [95% CI, 5.4–7.2] months per RECIST 1.1). The objective response rate was 23.3% per mRECIST and 16.7% per RECIST 1.1, while the disease control rate reached 76.7% per mRECIST/RECIST 1.1. The median overall survival was 16.0 (95% CI, 13.5–18.5) months. Treatment-related adverse events (TRAEs) occurred in 28 patients (93.3%) and grade 3 TRAEs were observed in 9 patients (30.0%). Conclusions Don-Sin showed promising antitumor effects with an acceptable safety profile in patients with advanced stage HCC. The preliminary findings need to be further evaluated in phase III randomized controlled trials. Trial registration ClinicalTrials.gov (identifier: NCT05162352; date of registration: December 4, 2021).